Hidup Berkelimpahan Dalam Perspektif Yohanes 10:10b - Sri Binar; Harman Ziduhu Laia; Jonathan Octavianus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
The abundant life in John 10:10b is understood in various ways. Prosperity theology adherents understand the abundant life which is the purpose of Christ's first coming into this world in a different way than others. The group understands that the 'abundance' (περισσὸν) in this text is material (worldly) abundance that Christ brings to every believer. Therefore there is an assumption that every believer should live with material abundance. Conversely, a believer whose life is materially poor will be considered to lack faith or sin which results in God not blessing him with material abundance. The methodology used in this study is the literature study method using exegesis principles based on Biblical hermeneutic laws. In-depth exegesis studies, based on textual, contextual, grammatical, structural, historical, literary, exegetical, and theological studies show that 'abundance' in the text is not an object (something) that believers get, but a description of how they get that object (eternal life). According to this text, the purpose of Christ's first coming is to bring eternal life to every believer in Him, and believers will very abundantly obtain eternal life. Really the coming, death, and resurrection of Christ are of no value if the goal is only to provide material abundance for each of His followers. ABSTRAK BAHASA INDONESIA Hidup berkelimpahan dalam Yohanes 10:10b dipahami dengan berbagai macam makna. Para penganut teologi kemakmuran memahami hidup berkelimpahan yang menjadi tujuan kedatangan pertama Kristus ke dalam dunia ini dengan cara yang berbeda dari yang lain. Kelompok tersebut memahami bahwa ‘kelimpahan’ (περισσὸν) dalam teks ini merupakan kelimpahan materi (duniawi) yang dibawa oleh Kristus bagi setiap orang percaya. Oleh karenanya ada anggapan seharusnya setiap orang percaya hidup dengan kelimpahan secara materi. Sebaliknya, orang percaya yang hidupnya miskin secara materi akan dianggap kurang beriman atau berdosa yang mengakibatkan Tuhan tidak memberkatinya dengan kelimpahan materi. Metodologi yang digunakan dalam penelitian ini adalah metode studi pustaka dengan memakai prinsip eksegesis berdasarkan hukum hermeneutik yang Alkitabiah. Studi eksegesis yang mendalam, berdasarkan studi tekstual, kontekstual, gramatikal, struktural, historikal, literatur, eksegetikal, dan teologi menunjukkan bahwa ‘kelimpahan’ dalam teks tersebut bukan objek (sesuatu hal) yang diperoleh orang percaya, melainkan keterangan bagaimana mereka memperoleh sebuah objek (hidup kekal) itu. Menurut teks ini, tujuan kedatangan pertama Kristus adalah membawa hidup kekal bagi setiap orang percaya kepada-Nya, dan orang percaya akan memperoleh dengan sangat melimpah hidup kekal itu. Sungguh kedatangan, kematian, dan kebangkitan Kristus sangat tidak bernilai jika tujuannya hanya untuk memberikan kelimpahan materi bagi setiap pengikut-Nya.